Navigating Negros the spatiality of history in selected works of Vicente Garcia Groyon - De Borja, Jean Aaron Doria (College of Arts and Letters, University of the Philippines Diliman, 2016)
The spatial turn in critical discourse signaled the re-emergence of space from the dominion of historicism. This study attempts to dismantle this hierarchy by analyzing three historical literary texts using spatial framework, thus drawing a strong connection between space and history. The works analyzed in this study - Rosario Cruz-Lucero's Feast and Famine: stories of Negros and La India, or Island of the Disappeared and Vicente Garcia Groyon's The Sky Over Dimas - use space to lay bare the problems and limitations of history. In using the concepts of space, place, mapping, the study shows that spatiality is far from the lifeless, unproductive analytical tool which traditional criticism has deemed it to be. The analysis shows that history possesses a latent spatiality which is able to bring into sharp focus its exclusionary, oppressive, and subjugating tendencies. Space and place are means to resists colonization, to unearth the forgotten past, and to reframe the telling of history.